Producing early modern London : a comedy of urban space, 1598-1616 - Stage, Kelly J., 1978- (Early modern cultural studies (Lincoln, Neb.), 2018)
"Early seventeenth-century London playwrights used actual locations in their comedies while simultaneously exploring London as an imagined, ephemeral, urban space. Producing Early Modern London examines this tension between representing place and producing urban space. In analyzing the theater's use of city spaces and places, Kelly J. Stage shows how the satirical comedies of the early seventeenth century came to embody the city as the city embodied the plays. Stage focuses on city plays by George Chapman, Thomas Dekker, William Haughton, Ben Jonson, John Marston, Thomas Middleton, and John Webster. While the conventional labels of "city comedy" or "citizen comedy" have often been applied to these plays, she argues that London comedies defy these genre categorizations because the ruptures, expansions, conflicts, and imperfections of the expanding city became a part of their form. Rather than defining the "city comedy," comedy in this period proved to be the genre of London. As the expansion of London's social space exceeded the strict confines of the "square mile," the city burgeoned into a new metropolis. The satiric comedies of this period became, in effect, playgrounds for urban experimentation. Early seventeenth-century playwrights seized the opportunity to explore the myriad ways in which London worked, taking the expected--a romance plot, a typical father-son conflict, a cross-dressing intrigue--and turning it into a multifaceted, complex story of interaction and proximity."--